Reduced expression of molecules of the cadherin/catenin complex in the transition from colorectal adenoma to carcinoma. - Hao, X; Palazzo, J; Ilyas, M; Tomlinson, I; Talbot, I (1997)
E-cadherin is crucial to the intercellular adherens junctions which are involved in the organisation and maintenance of epithelial structure and suppression of tumour invasion. E-cadherin is associated with the actin cytoskeleton via cytoplasmic proteins, including alpha-, beta- and gamma-catenins, which together form the cadherin/catenin complex. To evaluate changes of the molecules of the cadherin/catenin complex in colorectal carcinogenesis, seventy-four sporadic adenomas, samples of histologically normal epithelium adjacent to 65 adenomas, and 52 carcinomas arising in adenomas were investigated by immunohistochemistry. All normal epithelial cells showed a uniform membranous staining pattern for E-cadherin, alpha-, beta-, and gamma-catenin. Decreased expression of all 4 proteins occurred in parallel in adenomas and carcinomas (in all cases, p < 10(-5). Decreased expression of the cadherin/catenin complex in adenomas was associated with increasing severity of dysplasia (p < 0.001, for E-cadherin, alpha-, and gamma-catenin, p < 0.005 for beta-catenin). Carcinomas displayed significantly reduced expression of the cadherin/catenin complex compared with their associated adenomas (all p < 0.001). The results directly confirm that colorectal tumour progression and invasion is associated with disruption of the cadherin/catenin complex and suggest that the genetic changes and transcriptional modulation of catenins underlying this progression may affect all members of the complex.